Antecedent of WOM and Its Implications on The Brand Image of The Higher Education Institution in Bali - Yasa, Ni Nyoman Kerti; Giantari, I G. A. Ketut; Rahmayanti, Putu Laksmita Dewi; Tirtayani, I Gusti Ayu (JDM (Jurnal Dinamika Manajemen), 2021)
The purpose of this study is to explain the Antecedent of WOM and Its Implications on The Brand Image of The Higher Education Institution in Bali. The results showed that the variables tangible, re- sponsiveness, and empathy had a positive and significant effect on satisfaction, while reliability and as- surance had a positive and insignificant effect on satisfaction. Furthermore, satisfaction has a positive and significant effect on WOM and on brand image, and WOM has a positive and significant effect on brand image. In the future higher education institutions in Bali should increase reliability and assurance in order to increase satisfaction..